A Study of Giant Ovarian Tumors Presenting with Higher Incidence of Torsion: A Journey of my Experience in COVID-19 Pandemic at Tertiary Care Centre (Global Journal of Medical Research, 2021)
Abstract not found
Keywords: pandemic; torsion; COVID -19; huge ovarian tumor; gynecology; tumors